Parameters identification: a study case - Flores M., Sergio; Barahona P., Diego E.; Urbina M., E. Gerardo (Revista Mexicana de Ingenieria Biomedica, 2018)
A three-compartment model is proposed whose objective is to describe the kinetics of a certain type of medication. We studied the possibility of estimating all the unknown parameters that intervene in the model from samples of blood concentration, for a specific drug of interest.